Photo reduction of CO2 to methanol via TiO2 photocatalyst. (2005) - Wu, Jeffrey C. S.; Lin, Hung-Ming
Abstract : Greenhouse gas such asCO 2 is the primary cause of global warming. Alternative energy source should be provided without producing moreCO 2, such as solar energy. One of the best routes to remedyCO 2 is to transform it to hydrocarbons using photo reduction. In our study, CO 2 was photocatalytically reduced to produce methanol using a Hg lamp with wavelength 365 nm in a steady-state optical-fiber photo reactor. The optical-fiber photo reactor, comprised of near 120 Cu/TiO 2 -coated fibers, was designed and assembled to transmit and spread light uniformly inside reactor.TiO 2 film was coated on optical fiber using dip-coating method. Titania and Cu-loaded solutions were prepared by a thermal hydrolysis method. The thickness of Cu/TiO 2 film was 53 nm and consisted of very fine spherical particle with diameter of near 14 nm. The XRD spectra indicated the anatase phase of allTiO 2 and Cu/TiO 2 films. The wavelength of absorption edge was on 367 nm, equivalent to near 3.3 eV. Most active Cu species onTiO 2 surface wereCu 2 O clusters, and played an important role for the formation of methanol. The methanol yield increased with UV irradiative intensity. Photo activity increased with increasing Cu loadings. Maximum methanol rate was 0.45μ mole/g-cat hr using 1.2 wt%-Cu/TiO 2 catalyst under 16 W /cm 2 irradiation, 1.3 bar pressure ofCO 2, and 5000 seconds mean residence time. Higher than 1.2 wt% Cu loading gave less rate of methanol yield because of the masking effect ofCu 2 O clusters on the surface of TiO2.